2021
DOI: 10.32591/coas.ojer.0502.03141d
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus in the Children’s World: Discourses and Drawings

Abstract: More than 1.5 billion students and young people worldwide have been affected by school and university closings due to the COVID-19 outbreak. With the closure of schools due to the COVID-19 pandemic in Turkey, a free distance education system was launched by the Ministry of Education on 23 March 2020 with a national level television and internet-based curriculum. The opinions of the children who have just started primary school but whose school has been closed due to the pandemic in the spring term are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a study, children showed distance, cleanliness, mask, curfew, not being able to go to school, using a computer at home in their pictures (Foster et al, 2020). Duban and Sen (2021), in their study to determine the perspectives of primary school first grade students (half-past six-seven years old) about the Coronavirus and its effects, it awareness has been reached.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, children showed distance, cleanliness, mask, curfew, not being able to go to school, using a computer at home in their pictures (Foster et al, 2020). Duban and Sen (2021), in their study to determine the perspectives of primary school first grade students (half-past six-seven years old) about the Coronavirus and its effects, it awareness has been reached.…”
Section: Introductionmentioning
confidence: 99%